Self-assembly of (boron-dipyrromethane)-diphenylalanine conjugates forming chiral supramolecular materials. Issue 4 (8th January 2018) - Karikis, Kostas; Butkiewicz, Aleksandra; Folias, Fotios; Charalambidis, Georgios; Kokotidou, Chrysoula; Charisiadis, Asterios; Nikolaou, Vasilis; Nikoloudakis, Emmanouil; Frelek, Jadwiga; Mitraki, Anna; Coutsolelos, Athanassios G.
Abstract : The synthesis as well as the reversible self-assembly of a series of BDP-FF conjugates are described. ECD studies revealed the chiral nature of the obtained materials. Abstract : Herein, we present the synthesis of a series of boron-dipyrromethane (BDP) derivatives bearing diphenylalanine (FF) at their meso position via amide bond coupling. The BDP-FF bioconjugates are able to form self-assembled materials with different morphologies. By altering various parameters such as the protecting group of the FF peptide or the solvent system of the self-assembly process, we were able to obtain either fibrillar or spherical nanostructures. Furthermore, we confirmed that both the formation as well as the dissociation of the self-assemblies is a reversible procedure that can be achieved by simply altering the solvent mixture. Electronic circular dichroism (ECD) studies demonstrated a characteristic mirror image relationship regarding the FL FL and FD FD enantiomers, revealing the chiral nature of the obtained materials. Interestingly, an intense excitonic bisignate signal was observed in the ECD spectrum of the fibrillar structures, whereas the spherical assemblies remained ECD silent. What is more, the electronic circular dichroism studies were supported by quantum chemical calculations.